SALVINIA COAHUILENSIS NOV. SP. DEL CRETACICO SUPERIOR DE MEXICO (Ameghiniana, 2013)
A new fossil water fern, Salvinia coahuilensis Weber, is described from material of the Maestrichtian Olmos Formation, Coahuila, Mexico. This is the first pre-Tertiary species of Salvinia formally described on the basis of megafossils. The species belongs to the Section Carinatae Shaparenko, and is closely related to S. nigropunctata A. Br., a recent African form. The most similar fossil species is S. bjerringii Mathiesen, from Neogene deposits of Denmark. Some paleoecological data referring S. coahuilensis are given.